Mobility-Lifetime Products in Organic Infrared Photodiodes with Peak Absorption at 1550 nm - Seo, Bogyeom; Bills, Tyler; Mahalingavelar, Paramasivam; Kim, Woojo; Eun, Hyeong Ju; Kim, Jong H.; Azoulay, Jason D.; Ng, Tse Nga (Advanced Electronic Materials, 2025)
Infrared photodiodes based on organic semiconductors are promising for low-cost sensors that operate at room temperature. However, their realization remains hampered by poor device efficiency. Here, performance limitations are analyzed by evaluating the mobility-lifetime products and charge collection efficiency of devices operating in the shortwave infrared with a peak absorption at 1550 nm. Through complementary impedance and current-voltage measurements on devices with different donor-to-acceptor semiconductor ratios, a trade-off between mobility and recombination time and the need to balance between transport and interfacial charge transfer are observed. Thus, this study revisits the mobility-lifetime metric to shed new light on charge collection constraints in organic infrared photodiodes.
Keywords: 1550 nm; Charge collection efficiency; Device efficiency; Infrared photodiode; Low-cost sensors; Mobility-lifetime products; Organic infrared polymer; Organics; Peak absorption; Performance limitations; infrared photodiodes; mobility-lifetime products; organic infrared polymers